Professional learning for teaching at a research-intensive university: The need for a ‘care-full’ environment - Herman, N.; Bitzer, E.; Leibowitz, B. (South African Journal of Higher Education, 2018)
The participation of academics in professional learning opportunities for teaching plays an important role in promoting the desired outcomes of higher education teaching and learning. If university teachers pursuing a career in academia however perceive the environment as non-appreciative and non-supportive, in other words, ‘care-less’ to such endeavours, they could become demoralised as a result of human and emotional responses. The purpose of the reported research was to explore the influence of their environment on the decision-making of academics to participate in professional learning opportunities at one research-intensive university. It shows what impact the care-less treatment of teachers may have on their decisions to learn to teach. Findings indicate that academics do not perceive the existing institutional environment as “care-full” (Milligan and Wiles 2010) towards teaching or university teachers. Carving out a teaching career in a care-less environment appears to have a negative influence on academics’ decision-making for professional learning. One implication of these findings is that university management should realise that a care-full environment to enhance professional learning for teaching, certainly at research-intensive institutions, is essential for such professional learning, for individual academics and subsequently for students and society, to prosper.